2019
DOI: 10.1177/0969733019849454
|View full text |Cite
|
Sign up to set email alerts
|

Field-testing the Euro-MCD Instrument: Experienced outcomes of moral case deliberation

Abstract: Background: Moral case deliberation is a form of clinical ethics support to help healthcare professionals in dealing with ethically difficult situations. There is a lack of evidence about what outcomes healthcare professionals experience in daily practice after moral case deliberations. The Euro-MCD Instrument was developed to measure outcomes, based on the literature, a Delphi panel, and content validity testing. To examine relevance of items and adequateness of domains, a field study is needed. Aim: To descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…The Euro-MCD Instrument was tested in four field studies (De Snoo-Trimp J.C., Molewijk A.C., Svantesson M., Widdershoven G.A.M., De Vet H.C.W: Field-testing the Euro-MCD Instrument: Important outcomes according to participants before and after Moral Case Deliberation. Submitted) [20][21][22] and reflection on MCD outcomes in general was done in two additional studies [23,24] as shown in Table 1. With regards to the field studies, studies I-III involve answers of respondents to the question 'How important is this outcome according to you?…”
Section: Sources Of Data For the Revision: Six Euro-mcd Field Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Euro-MCD Instrument was tested in four field studies (De Snoo-Trimp J.C., Molewijk A.C., Svantesson M., Widdershoven G.A.M., De Vet H.C.W: Field-testing the Euro-MCD Instrument: Important outcomes according to participants before and after Moral Case Deliberation. Submitted) [20][21][22] and reflection on MCD outcomes in general was done in two additional studies [23,24] as shown in Table 1. With regards to the field studies, studies I-III involve answers of respondents to the question 'How important is this outcome according to you?…”
Section: Sources Of Data For the Revision: Six Euro-mcd Field Studiesmentioning
confidence: 99%
“…In all field studies, participation was voluntary and based on informed consent. More details regarding recruitment procedures and respondents' characteristics can be found elsewhere [20][21][22][23][24].…”
Section: Sources Of Data For the Revision: Six Euro-mcd Field Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In all eld studies, participation was voluntary and based on informed consent. More details regarding recruitment procedures and respondents' characteristics can be found elsewhere [20][21][22][23][24][25].…”
Section: Sources Of Data For the Revision: Six Euro-mcd Eld Studiesmentioning
confidence: 99%
“…Recently, we conducted several eld studies (see Table 1) using the Euro-MCD Instrument to assess whether healthcare professionals perceived the presented outcomes as important, to examine their experiences of outcomes and to examine the clustering of items of the instrument [20][21][22][23][24][25]. Based on this process of eld-testing, time is ripe to present a revision of the Euro-MCD instrument.…”
Section: Introductionmentioning
confidence: 99%